Cobalt-doped Ni-based sulfide complex as well as preparation method and application thereof

The preparation of cobalt-doped Ni-based sulfide complexes through two hydrothermal reactions has solved the problem of insufficient stability of Ni-based sulfide complexes in the prior art, achieved a significant improvement in the electrocatalytic stability of the oxygen evolution reaction, and enhanced its prospects for industrial application.

CN119593007APending Publication Date: 2025-03-11NINGXIA MEDICAL UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411932957.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

Smart Images

  • Figure CN119593007A_ABST
    Figure CN119593007A_ABST
Patent Text Reader

Abstract

The invention relates to a cobalt-doped Ni-based sulfide complex and a preparation method and application thereof.The preparation method of the cobalt-doped Ni-based sulfide complex comprises the steps that a first aqueous solution containing urea, ammonium fluoride and a cobalt source makes contact with foamed nickel, a first hydrothermal reaction is conducted, and a complex precursor is obtained; the molar weight of a cobalt source in the first aqueous solution is 2.4-7.2%, preferably 4-5%, of the molar weight of the foamed nickel, enabling the complex precursor to be in contact with a second aqueous solution containing a sulfur source, and carrying out a second hydrothermal reaction to obtain the cobalt-doped Ni-based sulfide complex. The oxygen evolution reaction electro-catalysis stability of the prepared cobalt-doped Ni-based sulfide complex is remarkably improved, and the industrial application prospect of the Ni-based sulfide complex is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrocatalysis technology, and in particular to a cobalt-doped Ni-based sulfide complex, a preparation method thereof, and an application thereof. Background Art

[0002] As a clean energy, hydrogen has zero pollution and high energy density (142.35 KJ kg -1 ) and other significant advantages, making it the best choice to replace fossil energy. Hydrogen production by water electrolysis is a green and economical method. The water produced after hydrogen combustion can be used again for water electrolysis to produce hydrogen, thereby realizing the recycling of resources. The water electrolysis process includes two half reactions: the oxygen evolution reaction (Oxygen Evolution Reaction, OER) at the anode and the hydrogen evolution reaction (Hydrogen Evolution Reaction, HER) at the cathode. Among them, OER becomes the bottleneck of water electrolysis due to its high overpotential. In order to improve the electrolysis efficiency, a suitable catalyst is needed to reduce the overpotential.

[0003] Our research group has previously developed a new type of Ni-based sulfide complex (see patent document CN117107287A), which has excellent OER electrocatalytic performance. However, in subsequent studies, it was found that the OER electrocatalytic stability of the complex was poor. In practical applications, the stability of the electrocatalyst is one of the important indicators that determine whether it can be industrially applied. For a catalyst, if it does not have excellent stability, it is difficult to achieve industrial application. Therefore, it is necessary to further improve the electrocatalytic stability of the Ni-based sulfide complex. Summary of the invention

[0004] The purpose of the first aspect of the present application is to provide a method for preparing a novel cobalt-doped Ni-based sulfide complex. The purpose of the second aspect of the present application is to provide a cobalt-doped Ni-based sulfide complex prepared by the preparation method of the first aspect. The purpose of the third aspect of the present application is to provide the use of a cobalt-doped Ni-based sulfide complex as an electrocatalyst for oxygen evolution reaction.

[0005] The first aspect of the present application provides a method for preparing a cobalt-doped Ni-based sulfide composite, comprising: A first aqueous solution containing urea, ammonium fluoride and a cobalt source is contacted with the nickel foam and subjected to a first hydrothermal reaction to obtain a composite precursor, wherein the molar amount of the cobalt source in the first aqueous solution is 2.4-7.2%, preferably 4-5%, of the molar amount of the nickel foam; The composite precursor is contacted with a second aqueous solution containing a sulfur source and subjected to a second hydrothermal reaction to obtain the cobalt-doped Ni-based sulfide composite.

[0006] In some embodiments, in the first aqueous solution, the molar ratio of urea to ammonium fluoride is 1:1.

[0007] In some embodiments, the molar ratio of the sulfur source in the second aqueous solution to the nickel foam is 1:(1.15-1.20), preferably 1:1.19.

[0008] In some embodiments, the cobalt source is cobalt nitrate hexahydrate, and the sulfur source is selected from at least one of sodium sulfide, thiourea, and thioacetamide.

[0009] In some embodiments, the reaction temperature of the first hydrothermal reaction is 110-130° C., and the reaction time is 10-14 hours.

[0010] In some embodiments, the reaction temperature of the second hydrothermal reaction is 180-220° C., and the reaction time is 10-14 hours.

[0011] The second aspect of the present application provides a cobalt-doped Ni-based sulfide composite prepared according to the aforementioned method.

[0012] In some embodiments, the prepared cobalt-doped Ni-based sulfide composite comprises: Nickel foam, Ni3S2 and Ni9S8 grown on the nickel foam, and Co doped into Ni3S2 and Ni9S8 lattices 2+ .

[0013] The third aspect of the present application provides the use of a cobalt-doped Ni-based sulfide complex as an electrocatalyst for oxygen evolution reaction.

[0014] Beneficial Effects The present application provides a method for preparing a cobalt-doped Ni-based sulfide complex. The method prepares the cobalt-doped Ni-based sulfide complex by two hydrothermal reactions. Compared with the non-doped Ni-based sulfide complex prepared by one hydrothermal reaction in the prior art, the electrocatalytic stability of the oxygen evolution reaction of the obtained cobalt-doped Ni-based sulfide complex is significantly improved, which greatly improves the industrial application prospects of the Ni-based sulfide complex. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 These are the XRD spectra of the composite precursors Ni(OH)2 / NF, Co-Ni(OH)2 / NF-2, Co-Ni(OH)2 / NF-1, and Co-Ni(OH)2 / NF-3 prepared in Examples 1-4, wherein (A) shows characteristic peaks in the range of about 5-80° at a 2θ angle, and (B) shows an enlarged view of characteristic peaks in the range of about 5-40° at a 2θ angle.

[0016] Figure 2 These are the XRD spectra of Ni9S8@Ni3S2, Co-Ni9S8@Ni3S2-0.2, Co-Ni9S8@Ni3S2-0.1, and Co-Ni9S8@Ni3S2-0.3 prepared in Examples 1-4, wherein (A) shows characteristic peaks within the 2θ angle range of approximately 5-80°, and (B) shows an enlarged view of characteristic peaks within the 2θ angle range of approximately 5-40°.

[0017] Figure 3 SEM photos and EDS test results of each product are shown, where (a)-(e) are SEM photos of Ni(OH)2 / NF, Ni9S8@Ni3S2, Co-Ni9S8@Ni3S2-0.1, Co-Ni9S8@Ni3S2-0.2, and Co-Ni9S8@Ni3S2-0.3, respectively; (f) is the SEM photo of Co-Ni9S8@Ni3S2-0.2 used for EDS test, and (g)-(i) are the EDS element distributions of Ni, Co, and S corresponding to the area shown in (f), respectively.

[0018] Figure 4 These are the TEM test results of Co-Ni9S8@Ni3S2-0.2 prepared in Example 2, where (a) is the TEM photo of Co-Ni9S8@Ni3S2-0.2, (b) is the HRTEM photo of Co-Ni9S8@Ni3S2-0.2, and (c) and (d) are the enlarged HRTEM photos corresponding to the selected areas "c" and "d" in Figure (b), respectively.

[0019] Figure 5 The XPS results of Co-Ni9S8@Ni3S2-0.2 prepared in Example 2 and the comparison between Co-Ni9S8@Ni3S2-0.2 and Ni9S8@Ni3S2 are shown. (a) is the full XPS spectrum of Co-Ni9S8@Ni3S2-0.2, (b) is the Ni 2p spectrum of Ni9S8@Ni3S2 and Co-Ni9S8@Ni3S2-0.2, (c) is the S 2p spectrum of Ni9S8@Ni3S2 and Co-Ni9S8@Ni3S2-0.2, and (d) is the Co 2p spectrum of Co-Ni9S8@Ni3S2-0.2.

[0020] Figure 6The OER test results of Ni9S8@Ni3S2, Co-Ni9S8@Ni3S2-0.2, Co-Ni9S8@Ni3S2-0.1, Co-Ni9S8@Ni3S2-0.3 and the composite precursor Co-Ni(OH)2 / NF-0.2 prepared in Examples 1-4 are shown, where (a) is the LSV diagram (without iR drop compensation) and (b) is the overpotential comparison (current density of 10 and 50 mA cm -2 ), (c) Tafel slope, (d) Nyquist impedance spectrum, (e) linear fitting diagram of capacitance current density change and scan rate, (f) Co-Ni9S8@Ni3S2-0.2 at 10 mA·cm -2 The current-time curve when .

[0021] Figure 7 The Ni9S8@Ni3S2 prepared in the comparative example is shown in Figure 2. -2 The current-time curve when . DETAILED DESCRIPTION

[0022] Preparation Example of Ni-based Sulfide Composite Pretreatment of Nickel Foam (NF) A NF sheet with a size of 1 cm×2 cm (about 1.04 mmol) was placed in a 1 M hydrochloric acid solution and ultrasonically cleaned for about 30 minutes to remove the metal oxide layer on the surface. It was then ultrasonically cleaned with acetone for about 30 minutes, rinsed with deionized water and anhydrous ethanol for 8 times in sequence, and finally anhydrous ethanol was added to make the liquid surface submerge the surface of the NF. The sheet was covered with a sealing film for later use.

[0023] Example 1 Undoped Ni-based sulfide composite (1) Hydrothermal synthesis of Ni(OH)2 / NF Urea (CO(NH2)2, 5 mmol) and ammonium fluoride (NH4F, 5 mmol) were added to 30 mL of deionized water and ultrasonicated for 30 minutes to form a transparent and uniform solution. The solution and four pre-treated NFs (1 cm×2 cm) were transferred to a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner, sealed, and hydrothermal reaction was carried out. The hydrothermal reaction time was 12 hours at a temperature of 120 °C. After the reaction was completed, the reactor was cooled to room temperature, the sample was taken out, washed three times with deionized water and anhydrous ethanol, placed in a vacuum drying oven, and dried overnight at 40 °C. The obtained product was Ni(OH)2 grown on NF, recorded as Ni(OH)2 / NF.

[0024] (2) Hydrothermal synthesis of Ni9S8@Ni3S2 Weigh 266 mg (3.5 mmol) of thiourea, dissolve it in 30 mL of deionized water, and stir to form a transparent, uniform, colorless solution. Transfer the thiourea solution and 4 pieces of Ni(OH)2 / NF obtained in step (1) to a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner, seal it, and perform a hydrothermal reaction. The hydrothermal reaction time is 12 hours at a temperature of 200 °C. After the reaction is completed, wait for the reactor to cool to room temperature, wash it three times with deionized water and anhydrous ethanol, and dry it in a vacuum drying oven at 40 °C. The product is a Ni9S8@Ni3S2 complex grown on NF, recorded as Ni9S8@Ni3S2.

[0025] Example 2 Co-doped Ni-based sulfide composite (1) Hydrothermal synthesis of Co-Ni(OH)2 / NF Urea (CO(NH2)2, 5 mmol), ammonium fluoride (NH4F, 5 mmol) and cobalt nitrate hexahydrate (Co(NO3)2·6H2O, 0.2 mmol) were added to 30 mL of deionized water and ultrasonicated for 30 minutes to form a transparent and uniform solution. The solution and four pre-treated NFs (1 cm×2 cm) were transferred to a stainless steel autoclave with a 50 mL polytetrafluoroethylene liner, sealed, and hydrothermal reaction was carried out. The hydrothermal reaction time was 12 hours at a temperature of 120 °C. After the reaction was completed, the reactor was cooled to room temperature, the sample was taken out, washed three times with deionized water and anhydrous ethanol, placed in a vacuum drying oven, and dried overnight at 40 °C. The obtained product was Co-doped Ni(OH)2 grown on NF, recorded as Co-Ni(OH)2 / NF-0.2.

[0026] (2) Hydrothermal synthesis of Co-Ni9S8@Ni3S2 Weigh 266 mg (3.5 mmol) of thiourea, dissolve it in 30 mL of deionized water, and stir to form a transparent, uniform, colorless solution. Transfer the solution and 4 pieces of the product Co-Ni(OH)2 / NF-0.2 obtained in step (1) to a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner, seal it, and perform a hydrothermal reaction. The hydrothermal reaction time is 12 hours at a temperature of 200 °C. After the reaction is completed, wait for the reactor to cool to room temperature, wash it three times with deionized water and anhydrous ethanol, and dry it in a vacuum drying oven at 40 °C. The product is a Co-doped Ni9S8@Ni3S2 composite grown on NF, recorded as Co-Ni9S8@Ni3S2-0.2.

[0027] Example 3 The Co-doped Ni-based sulfide composite was synthesized according to the scheme of Example 2, except that the amount of cobalt nitrate hexahydrate was changed to 0.1 mmol. The product obtained in step (1) was recorded as Co-Ni(OH)2 / NF-0.1, and the final product obtained in step (2) was recorded as Co-Ni9S8@Ni3S2-0.1.

[0028] Example 4 The Co-doped Ni-based sulfide composite was synthesized according to the scheme of Example 2, except that the amount of cobalt nitrate hexahydrate was changed to 0.3 mmol. The product obtained in step (1) was recorded as Co-Ni(OH)2 / NF-0.3, and the final product obtained in step (2) was recorded as Co-Ni9S8@Ni3S2-0.3.

[0029] Comparative Example The sample was prepared according to the method described in Example 1 of patent document CN117107287A, and the steps were as follows: Thiourea (CH4N2S, 8 mmol) was dissolved in 30 mL of deionized water to form a transparent solution, which was then transferred to a 50 mL autoclave. The NF (four pieces, 2 × 1 cm 2 ) was placed in an autoclave and hydrothermally vulcanized at 200 °C for 12 hours. The autoclave was then cooled to room temperature naturally, the product was taken out, washed three times with anhydrous ethanol, and dried. This product is referred to as Ni9S8@Ni3S2-comparison.

[0030] Characterization of Ni-based sulfide complexes X-ray diffraction (XRD) characterization Figure 1 The XRD patterns of the composite precursors prepared in each embodiment are shown in FIG. Figure 1 In (A), it can be clearly observed that the four samples have strong diffraction peaks at 44.5°, 51.8°, and 76.4°, corresponding to the metal nickel Ni 0 (JCPDS No. 04-0850) (111), (200) and (220) crystal planes. 0 In addition to the diffraction peaks at 19.1°, 33.3°, 38.8° and 59.7°, four diffraction peaks were observed, which were compared with the standard cards of Co(OH)2 (JCPDS No. 51-1731) and Ni(OH)2 (JCPDS No. 14-0117). As shown in the figure, these four diffraction peaks are very consistent with the standard spectrum peaks of Ni(OH)2 (JCPDS No. 14-0117), corresponding to its (001), (100), (101) and (110) crystal planes respectively. Locally enlarged XRD ( Figure 1As can be seen in (B), compared with the undoped sample, after adding different amounts of Co, the (110) diffraction peak of Ni(OH)2 shifts to the left to a certain extent. This is because Co 2+ The radius is larger than Ni 2+ The radius, Co 2+ After doping, the spacing between the crystal planes increased and the diffraction peak shifted to the left, confirming that Co-doped Ni(OH)2 was in situ grown on NF after the first hydrothermal step.

[0031] Figure 2 The XRD spectra of samples Ni9S8@Ni3S2 (Example 1), Co-Ni9S8@Ni3S2-0.1 (Example 3), Co-Ni9S8@Ni3S2-0.2 (Example 2), and Co-Ni9S8@Ni3S2-0.3 (Example 4) are shown. Figure 2 As can be seen in (A), all samples have a strong diffraction peak at about 44.5°, corresponding to metal nickel Ni 0 (JCPDS No. 04-0850) (111) crystal plane. Except Ni 0 In addition to the diffraction peaks of Ni3S2 (JCPDS No. 44-1418), a series of diffraction peaks were observed at 21.8°, 31.1°, 37.8°, 49.7° and 55.2°, corresponding to the (101), (110), (003), (113) and (122) crystal planes of Ni3S2 (JCPDS No. 44-1418), respectively. In addition, multiple diffraction peaks at around 27.2°, 41.5°, 43.1° and 50.8° correspond to the (202), (024), (043) and (153) crystal planes of Ni9S8 (JCPDS No. 22-1193), respectively. It is worth noting that in samples with different Co doping amounts, no diffraction peaks of Co-related compounds were found, and it is speculated that Co exists in the form of amorphous compounds or in the form of lattice doping. From the locally enlarged XRD pattern ( Figure 2 (B) It can be seen that compared with the undoped sample Ni9S8@Ni3S2, after adding different amounts of Co, the characteristic diffraction peaks of Ni3S2 and Ni9S8 shift to the left to a certain extent. - The ions will gradually replace the OH - , forming the corresponding sulfide. The above results show that Co 2+ It enters the crystal lattice of Ni3S2 and Ni9S8 by doping.

[0032] Scanning electron microscopy (SEM) characterization Figure 3 The SEM image of the synthesized material is shown in Figure 2. The NF after treatment has a smooth surface. The SEM image of the hydroxide precursor Co-Ni(OH)2 / NF is shown in Figure 2. Figure 3 As shown in (a), a large number of nanosheets grow on the surface of the NF, showing a staggered arrangement of nanosheets.

[0033] Figure 3 (b) shows the morphology of the undoped Co sulfide sample, namely Ni9S8@Ni3S2. Since no Co source is added at this time, the added sulfur source only reacts with the Ni of the NF, so the NF is highly sulfurized. At this time, the flake morphology of the sample is maintained, but the thickness of the flake increases, and the flakes show irregular stacking morphology.

[0034] The flaky morphology changes significantly when Co sulfide is added. When the Co dosage is 0.1 mmol, the NF is still sulfided due to the small amount of Co source. A large amount of micron-shaped material can be seen on the NF framework, and some NF frameworks are broken, indicating that the stability of the NF framework will be destroyed due to the large amount of sulfidation, which has an adverse effect on the subsequent electrocatalytic reaction ( Figure 3 (c)).

[0035] When the amount of Co increased to 0.2 mmol, the amount of material grown on the NF framework decreased compared to the 0.1 mmol Co doped sample, which is presumably due to the reduced degree of NF sulfidation, which kept the NF framework in good condition. The morphology of the sample is still micron flower-like. Compared with the 0.1 mmol Co sample, the size of the flower is slightly reduced, but the edges and corners of each branch of the flower become clearer ( Figure 3 (d)).

[0036] When the Co doping amount increases to 0.3 mmol, the sulfidation degree of NF is further reduced due to the reaction of more Co salt with sulfur, and the sulfide growth on NF is further reduced ( Figure 3 (e)). The sample still has a flower-like morphology, but the flowers are severely aggregated, which reduces the surface area.

[0037] It can be seen that the appropriate amount of Co doping can adjust the sulfidation degree of NF and the morphology of the sample: when the Co doping amount is less, the sulfidation degree of NF is higher, the mechanical stability of the NF framework is poor, which is not conducive to the subsequent electrocatalytic stability test; when the Co doping amount is higher, the NF sulfidation degree is lower, the growth of sulfide is less, and the electrocatalytic performance is poor. When the Co doping amount is 0.2 mmol, the Co-Ni9S8@Ni3S2-0.2 complex has the best sulfide content and morphology, which is conducive to improving the electrocatalytic activity and stability.

[0038] EDS (Energy Dispersive X-ray Spectroscopy) test results ( Figure 3 (f)-(i)) prove that the three elements Ni, Co, and S coexist and are evenly distributed in the sample Co-Ni9S8@Ni3S2-0.2.

[0039] Transmission electron microscopy (TEM) characterization Figure 4 (a) is a TEM image of the sample of Co-Ni9S8@Ni3S2-0.2 prepared in Example 2 obtained by ultrasonic treatment in ethanol, showing that the micron flower-like morphology is composed of nanosheet structures. Figure 4 (b) is a high-resolution transmission electron microscopy (HRTEM) image of Co-Ni9S8@Ni3S2-0.2, which clearly shows the existence of the phase interface. Figure 4 (b) HRTEM magnification of the selected area. Figure 4 In (c), lattice fringes with a spacing of 0.291 nm can be observed, corresponding to the (110) crystal plane of Ni3S2. Figure 4 In (d), lattice fringes of 0.474 nm can be observed, corresponding to the (002) plane of Ni9S8 (a small amount of Co doping will change the interplanar spacing, but the deviation is very small). These interplanar spacings are consistent with the XRD results discussed above, thus proving that a Ni9S8@Ni3S2 complex with Ni3S2 and Ni9S8 phases was successfully formed on the NF surface.

[0040] X-ray photoelectron spectroscopy (XPS) characterization XPS characterization was performed to analyze the valence state and chemical environment of the elements in the prepared Co-Ni9S8@Ni3S2-0.2. Before fitting, all peak positions were corrected using the C1s peak (284.8 eV). The results are shown in Figure 5 . Figure 5 (a) is the full XPS spectrum of Co-Ni9S8@Ni3S2-0.2, proving the presence of three elements: Co, Ni and S. Figure 5 In (b), the binding energies of 855.3 and 873.0 eV in Ni9S8@Ni3S2 correspond to Ni 2+ 2p 3 / 2 and Ni 2+ 2p 1 / 2 , the higher binding energies at 856.9 and 874.8 eV correspond to Ni 3+ 2p 3 / 2 and Ni 3+ 2p 1 / 2 Calculating the integral area of ​​the fitting curve shows that Ni in Ni9S8@Ni3S2 3+ with Ni 2+ The peak area ratio is 0.33; in the Co-doped sample Co-Ni9S8@Ni3S2, Ni 2+ and Ni 3+ The peak position of Ni9S8@Ni3S2 is the same as that of Ni9S8@Ni3S2, except that Ni 3+ with Ni 2+The peak area ratio increases to 0.47, indicating that the content of trivalent nickel ions increases after Co doping, and there is electron transfer from Ni to other elements (Co or S). Figure 5 In (c), for Co-Ni9S8@Ni3S2-0.2, the peaks with binding energies of 161.7 and 163.1 eV are attributed to S 2- 2p 3 / 2 and S 2- 2p 1 / 2 The signal at 168.7 eV corresponds to oxidized sulfur species (SO), which originates from the partial oxidation of the material surface in air. It is worth noting that compared with the undoped Ni9S8@Ni3S2, the S 2p 3 / 2 and 2p 1 / 2 The negative shift of 0.3 eV and the decrease in S binding energy indicate that electrons are transferred from other atoms to S, indicating that Co doping causes this electron transfer. Combined with the above analysis, Co doping may lead to electron transfer from Ni to S, an increase in the electron cloud density on the S atom, and a decrease in the electron cloud density of the Ni ion, which in turn causes Ni 3+ The proportion of Ni 3+ It is the active site of the OER intermediate *OH, so the electron transfer from Ni to S will be beneficial to the improvement of OER performance. Figure 5 In (d), the peaks at 781.3 and 796.7 eV correspond to Co 2+ 2p 3 / 2 and Co 2+ 2p 1 / 2 , the peaks at 777.8 and 795.0 eV correspond to Co 3+ 2p 3 / 2 and Co 3+ 2p 1 / 2 The presence of Co XPS signal also proves the existence of Co in Co-Ni9S8@Ni3S2-0.2.

[0041] OER catalytic performance test of Ni-based sulfide complex The OER performance of Ni9S8@Ni3S2, Co-Ni9S8@Ni3S2-0.2, Co-Ni9S8@Ni3S2-0.1, Co-Ni9S8@Ni3S2-0.3 prepared in Examples 1-4 and the composite precursor Co-Ni(OH)2 / NF-0.2 were tested.

[0042] The electrochemical test adopts a standard three-electrode system. The NF-based composite material synthesized in each example can be directly used as the working electrode (the sample is fixed with an electrode clamp so that the area immersed in the electrolyte is 1 cm 2), platinum electrode as counter electrode, Hg / HgO electrode as reference electrode, electrolyte as 1 M KOH solution, all test results were not corrected for iR. Nitrogen was passed through the electrolyte for 30 minutes before the test to eliminate the interference of dissolved oxygen.

[0043] The polarization curve was tested by linear sweep voltammetry (LSV) with a scan rate of 5 mV / s. Figure 6 As shown in (a) and (b), for Co-Ni9S8@Ni3S2- x (x=0.1, 0.2, 0.3) series samples, up to 10mA cm -2 The overpotential required for the current density ( η 10 ) is between 160 and 190 mV, which is much lower than the overpotential of the first step product Co-Ni(OH)2 / NF-0.2 ( η 10 = 407mV) and the overpotential of Co-free Ni9S8@Ni3S2 ( η 10 = 195 mV). The improvement in catalytic activity can be attributed to the heterogeneous interface formed between Ni9S8 and Ni3S2, as well as the optimization of the electronic structure of the elements (Ni, S) by Co doping, all of which are conducive to improving the catalytic performance. With the increase in the amount of Co doping, the overpotential shows a trend of first decreasing and then increasing, that is, the OER activity first increases and then decreases. Among them, Co-Ni9S8@Ni3S2-0.2 has the best performance. η 10 and η 50 160 mV and 275 mV respectively, which are significantly lower than those of Co-Ni9S8@Ni3S2-0.1 ( η 10 = 191 mV, η 50 = 341 mV), Co-Ni9S8@Ni3S2-0.3 ( η 10 = 165 mV, η 50 =305 mV). This indicates that the amount of Co source added in the first step of the hydrothermal reaction has a significant effect on the final performance of the catalyst. An appropriate amount of Co doping helps to form a morphology with a larger specific surface area and expose more catalytic active sites. Therefore, when preparing Co-Ni9S8@Ni3S2 in this application, the Co doping amount (0.1 mmol, 0.2 mmol, 0.3 mmol) is preferably 0.2 mmol.

[0044] The Tafel slope of the sample can be obtained from the LSV curve. Figure 6As shown in (c), compared with the first step sample Co-Ni(OH)2 / NF-0.2 (Tafel slope is 156 mV dec -1 ) and Ni9S8@Ni3S2 (Tafel slope is 90 mV dec -1 ), the Tafel slope of the Co-doped material is smaller (51-87 mV dec -1 ), and the Tafel slope of Co-Ni9S8@Ni3S2-0.2 is the smallest, which is 51 mV dec -1 , indicating that it has the fastest OER kinetic rate.

[0045] Electrochemical impedance spectroscopy (EIS) was used to study the charge transfer resistance of different samples. The Nengquist impedance spectra of the synthesized samples were tested in the frequency range of 0.01 Hz to 100 kHz. The results are as follows: Figure 6 As shown in (d). By comparing the radius and resistance of the semicircle in the low-frequency region, it can be seen that compared with Co-Ni(OH)2 / NF and Ni9S8@Ni3S2, the R ct The impedance R of Co-Ni9S8@Ni3S2-0.1, Co-Ni9S8@Ni3S2-0.2, and Co-Ni9S8@Ni3S2-0.3 is smaller, especially Co-Ni9S8@Ni3S2-0.2, which has the smallest charge transfer resistance, indicating that its electron transfer rate in the OER process is the fastest. ct They are 8.65 Ω, 2.83 Ω, and 3.82 Ω respectively. See Table 1 for specific data.

[0046]

[0047] Through cyclic voltammetry experiments, we obtained the electrochemical double layer capacitance (C dl ), this capacitance value is proportional to the electrochemically active surface area (ECSA), so it can be calculated by C dl To estimate the ECSA of the sample. Figure 6 As can be seen in (e), sample C dl The order of values ​​is: Co-Ni9S8@Ni3S2-0.2 (9.8 mF cm -2 )> Co-Ni9S8@Ni3S2-0.3 (9.1 mF cm -2 )> Co-Ni9S8@Ni3S2-0.1 (6.4 mF cm -2 )> Ni9S8@Ni3S2 (5.9 mF cm -2 )> Co-Ni(OH)2 / NF-0.2 (4.9 mF cm -2). The above results show that compared with the undoped Ni9S8@Ni3S2, the active surface area of ​​the doped samples is significantly increased, which can improve the OER performance. Among the three Co-doped Ni9S8@Ni3S2, the C dl The value is the largest, indicating that it has the largest electrochemically active surface area.

[0048] In order to realize the practical application of electrocatalysts, high stability is very important. The chronoamperometric (IT) method was used to investigate the electrocatalytic performance of Co-Ni9S8@Ni3S2-0.2 at a current density of 10 mA cm -2 The OER stability test was conducted under the condition of setting the voltage to 1.46 V vs. RHE. The results are shown in Figure 6 As shown in (f), there is no obvious decay in the current density after 48 h of electrolysis, indicating that the material has excellent OER electrocatalytic stability.

[0049] As a control, the Ni9S8@Ni3S2- contrast At a current density of 10 mA cm -2 The OER stability under Figure 7 As shown. Ni9S8@Ni3S2- contrast The stability is poor. As the electrolysis time increases, a large amount of black matter falls off from the electrolytic cell during the experiment. Figure 7 It can also be seen that Ni9S8@Ni3S2- contrast After 5 h of electrolysis, the current density has dropped significantly, indicating that the stability of this catalyst needs to be strengthened.

[0050] contrast Figure 6 Middle (f) and Figure 7 It can be seen that the cobalt-doped Ni-based sulfide complex prepared by the two-step hydrothermal method in the present application is significantly improved in OER stability compared to the undoped Ni-based sulfide complex prepared by the one-step hydrothermal method in the comparative example.

[0051] The above description is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing a cobalt-doped Ni-based sulfide composite, characterized in that: include: A first aqueous solution containing urea, ammonium fluoride and a cobalt source is contacted with the nickel foam and subjected to a first hydrothermal reaction to obtain a composite precursor, wherein the molar amount of the cobalt source in the first aqueous solution is 2.4-7.2%, preferably 4-5%, of the molar amount of the nickel foam; The composite precursor is contacted with a second aqueous solution containing a sulfur source and subjected to a second hydrothermal reaction to obtain the cobalt-doped Ni-based sulfide composite.

2. The preparation method according to claim 1, characterized in that: In the first aqueous solution, the molar ratio of urea to ammonium fluoride is 1:

1.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of the sulfur source in the second aqueous solution to the nickel foam is 1:(1.15-1.20), preferably 1:1.

19.

4. The preparation method according to claim 1 or 2, characterized in that: The cobalt source is cobalt nitrate hexahydrate, and the sulfur source is selected from at least one of sodium sulfide, thiourea, and thioacetamide.

5. The preparation method according to claim 1 or 2, characterized in that: The reaction temperature of the first hydrothermal reaction is 110-130° C., and the reaction time is 10-14 hours.

6. The preparation method according to claim 1 or 2, characterized in that: The reaction temperature of the second hydrothermal reaction is 180-220° C., and the reaction time is 10-14 hours.

7. The cobalt-doped Ni-based sulfide composite prepared by the preparation method according to any one of claims 1 to 6.

8. The cobalt-doped Ni-based sulfide composite according to claim 7, comprising: Nickel foam, Ni3S2 and Ni9S8 grown on the nickel foam, and Co doped into Ni3S2 and Ni9S8 lattices 2+ .

9. Use of the cobalt-doped Ni-based sulfide composite according to claim 7 or 8 as an electrocatalyst for oxygen evolution reaction.

Citation Information

Patent Citations

  • Ni-based sulfide complex as well as preparation method and application thereof

    CN117107287A